Immune profiling of a patient with alemtuzumab-associated progressive multifocal leukoencephalopathy. (July 2019) - Gerevini, Simonetta; Capra, Ruggero; Bertoli, Diego; Sottini, Alessandra; Imberti, Luisa
A 31-year-old woman affected by multiple sclerosis (MS) experienced generalized tonic–clonic seizures 2 months after the second alemtuzumab cycle. Positive JC virus (JCV)-DNA in cerebrospinal fluid (CSF) and lesion iconography at magnetic resonance imaging (MRI) were suggestive of progressive multifocal leukoencephalopathy (PML). After 1 month, during full-blown immune reconstitution inflammatory syndrome, JCV-DNA became negative and symptoms gradually improved. New T- and B-cell output and T- and B-cell diversity were low and lymphocytes poorly responded to stimulation. This is the first case of an alemtuzumab-treated patient with clinical symptoms and radiological features compatible with PML. The lack of large T- and B-cell diversity, necessary for JCV recognition, is likely to have concurred to PML insurgence.